Effect of atrial fibrillation on perfusion changes in the posterior segment of the eye - Piejko, Piotr (2022)
The aim of the study The aim of the study is to analyze the impact of atrial fibrillation (AF) on blood flow (blood perfusion) in the posterior segment of the eye in patients treated with anticoagulants, using new technology optical coherence tomography angiography (OCT-A) based on own experimental data and literature reports. The study is focused on the dependence of blood perfusion on the type of anticoagulant used in the treatment. Method 30 patients with NYHA class I and ll with permanent atrial fibrillation (New York Heart Association Heart Failure Classification) were recruited. All the patients underwent the TTE examination. In each patient a series of measurements of the central part of the retina was carried out, evaluating the parameters of blood perfusion using the Zeiss AngioPlex OCT Cirrus 5000 angiography platform with the FastTracTM function. Results In patients with atrial fibrillation and NYHA class I and II heart failure the density of vessels in both eyes was significantly lower than in healthy individuals (with no atrial fibrillation). In healthy individuals the vessel density was considerably higher than in patients treated with Warfarin, Acenocumarol and Dabigatran. The exception is Rivaroxaban. In patients taking three drugs - Warfarin, Acenocumarol and Dabigatran the vessel density was significantly lower than in healthy individuals. In patients tre
Keywords: OCT angiography - echocardiography; anticoagulant therapy; atrial fibrillation; retinal microcirculation